Effect of chemical composition and T6 heat treatment on the mechanical properties and fracture behaviour of Al-Si alloys for IC engine components - Vuksanovic, Darko; Asanovic, Vanja; Scepanovic, Jelena; Radonjic, Dragan (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
Two Al-Si alloys intended for application in IC engine components have been studied. The dendrites of α-Al phase, eutectic silicon and several intermetallic phases were revealed in all samples. Besides, the polyhedral crystals of the primary silicon were observed in the as-cast hypereutectic Al-12.5Si alloy. A better tensile strength and elongation were recorded for specimens of the Al-11Si compared to the Al-12.5 Si alloy. The predominantly intercrystalline fracture with features of ductile failure was observed in both alloys. In as-cast specimens of Al-11Si alloy, the cracks are formed by the decohesion mechanism between the particles of intermetallic phase AlCuFeNi and α-Al phase. The microcracks initiated on the boundary surface were spread along the branches of α-Al15(Fe,Mn,Cu)3Si2 particles with Chinese script shape. The dimple areas were larger after heat treating of specimens of Al-11Si alloy. The primary silicon crystals in the as-cast specimens of alloy Al-12.5Si contributed to a greater brittleness compared to cast Al-11Si alloy. The microcracks in those samples were formed by the fracture of the primary silicon crystals and massive particles of star-like and polyhedron forms of the Al3(Fe,Mn,Cu,Ni,Co) phase. The ductility of the Al-12.5 alloy was improved by means of the T6 treatment.